Pemerintahan daerah Sumatera Barat dari VOC hingga reformasi - Asnan, Gusti (Yogyakarta : Citra Pustaka, 2006)
History of local government in Sumatera Barat Province from the period of the Nederlandsche Oost-Indische Compagnie, the colonial period up to the present.
Includes bibliographical references (p. [271]-277).
Keywords: Local government -- Indonesia -- Sumatera Barat -- History